Thrombectomy with low ASPECTS: the roles of infarct volume and postacute neurological status - Kniep, Helge; Gellißen, Susanne; Thomalla, Götz; Bendszus, Martin; Winkelmeier, Laurens; Broocks, Gabriel; Bechstein, Matthias; Subtil, Fabien; Bonekamp, Susanne; Aamodt, Anne Hege; Fuentes, Blanca; Gizewski, Elke R.; et al. (Stroke, 2025)
BACKGROUND: - Recent randomized trials demonstrated the beneficial effect of endovascular therapy in patients with low Alberta Stroke Program Early CT Score. Despite large follow-up infarct volumes, a significantly increased rate of good functional outcomes was observed, challenging the role of infarct volume as a predictive imaging marker. This analysis evaluates the extent to which the effects of endovascular thrombectomy on functional outcomes are explained by (1) follow-up infarct volume and (2) early neurological status in patients with stroke with low Alberta Stroke Program Early CT Score. - METHODS: - TENSION (Efficacy and Safety of Thrombectomy in Stroke With Extended Lesion and Extended Time Window) was a randomized trial conducted from February 2018 to January 2023 across 41 stroke centers. Two hundred fifty-three patients with ischemic stroke due to anterior circulation large vessel occlusion and Alberta Stroke Program Early CT Score of 3 to 5 were randomized to endovascular thrombectomy plus medical treatment or medical treatment alone. All patients with the availability of relevant data points were included in this secondary as-treated analysis. The primary outcome was the 90-day modified Rankin Scale score. Confounder-adjusted mediation analysis was performed to quantify the proportion of the treatment effect on a 90-day modified Rankin Scale score explained by (1) 24-hour follow-up infarct volume and (2) 24-hour National Institutes of Health Stroke Scale scores. - RESULTS: - One hundred eighty-eight patients were included; thereof, 87 (46%) were female patients. Median age was 72 (interquartile range, 63-79) years. The endovascular thrombectomy cohort had a 20.5 (95% CI, 8.3-33.7) percentage points higher probability of achieving independent ambulation (modified Rankin Scale, 0-3) and a 24.2 (95% CI, 13.4-35.8) percentage points lower mortality at 90 days compared with medical treatment alone. The reduction in 24-hour follow-up infarct volume explained 30% of the treatment effect on functional outcomes, while the 24-hour National Institutes of Health Stroke Scale score explained 61%. - CONCLUSIONS: - In patients with low Alberta Stroke Program Early CT Score, infarct volume demonstrated limited explanatory power for functional outcomes compared with the early neurological status, which may more effectively reflect factors such as the involvement of specific brain regions, disruption of structural networks, and selective neuronal loss.
Gesehen am 17.11.2025